The king & I : the uncensored tale of Luciano Pavarotti's rise to fame by his manager, friend, and sometime adversary /: the uncensored tale of Luciano Pavarotti's rise to fame by his manager, friend, and sometime adversary. (2011) - Unknown
No abstract available